108k views
5 votes
What is the solution to
the following equation?
-x - 6(x-5) = 86

2 Answers

4 votes

Answer:

x = -8

Explanation:

-x -6(x-5) = 86

Distribute

-x -6x +30 = 86

Combine like terms

-7x + 30 =86

Subtract 30 from both sides

-7x = 56

Divide by -7

x = -8

User Gtomika
by
5.1k points
3 votes

Answer:

Explanation:

Simplify the terms first also what is the question asking what x is equal to? or just to simplify the terms~ if u answer this i can help more dm me maybe~!

User Neil Vass
by
5.1k points